Risk factors for human fascioliasis in schoolchildren in Baños del Inca, Cajamarca, Peru - Rodríguez-Ulloa C. (2018)
BackgroundThe aim of the investigation was to determine the risk factors for human fascioliasis in schoolchildren in five localities of the Baños del Inca district in Cajamarca, Peru. Secondarily, the prevalence of infection among this population was also studied.MethodsA questionnaire was applied to 270 schoolchildren from 6–12 years of age and to their parents with the aim of collecting information related to risk factors predisposing the children to Fasciola hepatica infection. Faecal samples from all the children were tested for F. hepatica using the modified rapid sedimentation method of Lumbreras and the technique of Kato–Katz for egg counts.ResultsRisk factors were identified as follows—raising cattle, consumption of radishes and chewing grass. The prevalence of F. hepatica in Baños del Inca was 6.30%; there was no significant difference by sex or age.ConclusionRisk factors associated with this parasitosis in children in this area of Cajamarca were the raising of cattle, the consumption of radish and the habit of chewing grass. The prevalence results in this district suggest a mesoendemic level of infection, with local variations between meso- and hyper-endemic levels.